CSR activities and consumer loyalty: the effect of the type of publicizing medium - Mercadé-Melé, Pere; Molinillo, Sebastian; Fernández-Morales, Antonio; Porcu, Lucia (Journal of Business Economics and Management, 2018)
This research develops a model to predict the effect of advertising a socially responsible activity on perceived corporate social responsibility (CSR) and its influence on consumer loyalty. It examines the relationships between company-cause congruence, corporate credibility, altruism attribution and perceived CSR, and CSR with consumer loyalty, and analyzes the moderating effect of the type of communication medium (i.e. traditional medium vs. social medium). This study is original because it fills the gap in the CSR communication literature in the evaluation of how the use of one or another type of medium to advertise a cause related marketing activity influences the effect of perceived CSR on consumer loyalty. An empirical study was conducted with two samples of consumers, each of which was exposed to the same advertisement, inserted in either a newspaper or posted on a social network. Data were analyzed using structural equation modeling. The results carry implications for CSR activities and communications management as they validate the proposed model that integrates the antecedents of perceived CSR and its influence on loyalty, and show that the traditional medium model has a better fit and its overall effect is greater than the social medium model. From a practical perspective, this study has several implications regarding the importance of communicating CSR activities.